Production of a panel of monoclonal antibodies against the nucleocapsid protein of heat resistant Newcastle disease virus - Ahmad Raus, Raha; Ali, Abdul Manaf; Tan, Wen Siang; Mohd. Salleh, Hamzah; Eshagi, Majid; Yusoff, Khatijah (2007)
A panel of six monoclonal antibodies against the nucleocapsid protein (NP) of Newcastle disease virus (NDV) strain AF2240 was produced by immunization of Balb/c mice with purified NP. Isotyping test revealed three of the monoclonal (mAbs) were IgG1 and the others were IgG2a. All of the mAbs recognized linearized NP epitopes. The reactivity of these mAbs with local isolates revealed that three mAbs recognized conserved antigenic sites and the others bind to antigenic sites which undergone considerable changes.